Frequency of Urinary Tract Infections and Their Antibacterial Susceptibility among Chronic Kidney Disease Patients Undergoing Hemodialysis - Hidayatullah Memon; Parkash, Om; Kumar Gumnani, Vijia (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To investigate the prevalence and antibiotic resistance of uropathogenic bacteria among chronic kidney disease (CKD) patients undergoing hemodialysis. METHODOLOGY: This descriptive, cross-sectional study was conducted at Chandka Medical College, Larkana, from May 2023 to September 2024. Using a convenient sampling technique, the study included 187 patients diagnosed with CKD, aged between 15 and 74 years of both genders, undergoing hemodialysis, including those with stone disease, neurogenic bladder dysfunction, or urinary tract foreign bodies. Patients with a history of urinary tract malignancy, congenital anomaly of the urogenital tract, recent antibiotic use or unwillingness to participate were excluded. Data was collected via a structured questionnaire. Urine samples were cultured on cystine-lactose-electrolyte-deficient (CLED) agar, and uropathogenic bacteria were identified using Gram staining and biochemical tests. Antibiotic susceptibility was determined using the Kirby-Bauer method, and the data were analysed with SPSS (version 24.0). RESULTS: Majority of patients (51.2%) were aged 50–60 years. Urinary tract infections (UTIs) were identified in 84 (45%) patients. The most common pathogens were Escherichia coli (E. coli) (42.8%), Klebsiella spp. (35.7%), and Proteus spp. (21.4%). No significant association was observedbetween gender and the occurrence of urinary tract infection (UTI). Amikacin demonstrated 100% sensitivity against E. coli and Klebsiella spp. High resistance rates were observed for ceftazidime, norfloxacin, and amoxicillin. CONCLUSION: UTIs are highly prevalent among CKD patients undergoing hemodialysis. The emergence of significant antimicrobial resistance (AR) highlights the need for routine susceptibility testing and strengthened antibiotic stewardship programs.